Hubungan Dukungan Teman Sebaya Dengan Tingkat Kecemasan Mahasiswa Sebelum Ujian OSCE Fakultas Farmasi Dan Ilmu Kesehatan Universitas Abdurrab Tahun 2025 - Yulia Febrianita; Nadhifa Zahwa Putri (LPPM Universitas Abdurrab, 2026)
The Objective Structured Clinical Examination (OSCE) is a clinical competency evaluation that can cause anxiety among students. In OSCE, students are assessed through a series of practical stations evaluating skills, decision-making, and communication. This study aimed to examine the relationship between peer support and anxiety levels among students before the OSCE at the Faculty of Pharmacy and Health Sciences, Universitas Abdurrab in 2025. This quantitative study used a correlational design. The population consisted of 252 first-year students from Nursing, Midwifery, Physiotherapy, and Medical Laboratory Technology programs, with a sample of 155 respondents selected using cluster sampling. Data were collected using a peer support questionnaire (adapted from Khasanah) with 20 items and the Zung Self-Rating Anxiety Scale (ZSAS) with 18 items. The results showed that most respondents had high peer support (90 students, 58.1%) and severe anxiety (92 students, 59.4%). Chi-square test results showed p = 0.000 (p < 0.05), indicating a significant relationship between peer support and students’ anxiety levels before the OSCE. The study recommends enhancing peer support programs, such as mentoring, study groups, or peer counseling activities, to help students reduce anxiety before facing the OSCE.